Modeling and Simulation of Carbon Dioxide Gas Reactive Desorption Process with Piperazine Promoted Diethanolamine Solvent in Sieve Tray Column - Nur Ihda Farikhatin Nisa; Nabila Farras Balqis; Muhammad Anshorulloh Mukhlish; Ali Altway; Mahfud Mahfud (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Carbon dioxide (CO2) is an acidic and corrosive gas, and the presence of this gas in the piping system can cause various problems in the industrial sector. Therefore, the CO2 must be separated from the gas stream. One of the CO2 gas separation processes from the gas stream is carried out in a CO2 removal unit, where a desorption unit serves as a solvent regeneration step. Therefore, this study aims to develop a rate-based model and simulation of the reactive desorption process of CO2 gas in a sieve tray column. The rate-based model in the reactive desorption process of CO2 gas is based on film theory, the liquid in the tray is assumed completely agitated due to gas bubbling, the flow pattern of gas is plug flow, and the effect of the reaction on the mass transfer follows the enhancement factor concept. The number of trays used in this study was 20. In addition, the effect of several variables, such as: desorber pressure, rich amine temperature, rich amine flow rate, and reboiler load, was also assessed on the CO2 stripping efficiency. The accuracy of our prediction model is 1.34% compared with industrial plant data. Compared with the chemical engineering simulator simulation results, the average deviation is 4%. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).